Triptorelin Peptide Conjugated Alginate Coated Gold Nanoparticles as A New Contrast Media for Targeted Computed Tomography Imaging of Cancer Cells - Mohammad Danesh-Doust; Rasoul Irajirad; Fereshteh Vaziri Nezamdoust; Sara Khademi; Alireza Montazerabadi (Cell Journal, 2023)
Objective: Increasing research has been focused on the development of various nanocomplexes as targeted contrastmedia in diagnostic modalities, mainly in computed tomography (CT) scan imaging. Herein, we report a new methodthat uses Triptorelin [a luteinizing hormone-releasing hormone (LHRH) agonist]-targeted gold nanoparticles (AuNPs)via alginate for early detection of cancer by molecular CT imaging.Materials and Methods: In the experimental study, the formed multifunctional AuNPs coated with alginate conjugatedwith Triptorelin peptide (Triptorelin-Alginate-AuNPs) were synthesized and characterized via different techniques,including transmission electron microscopy (TEM), dynamic light scattering (DLS), and fourier transform infrared (FTIR)spectroscopy. The MTT assay was applied to calculate the toxicity of the NPs.Results: The results indicated that the formed Triptorelin-Alginate-AuNPs with an Au core size of ~18 nm arenoncytotoxic at 127-, 254-, 381- and 508-mM concentrations and revealed significant improvement in the attenuationof X-rays intensity and contrast to noise ratio (CNR), compared with non-targeted cells at the highest energies (90, 120,140 kVp). At 90 kVp, compared to non-targeted cells, targeted cells (Triptorelin-Alginate-AuNPs) enable 1.58, 1.69, 3.7and 3.43 times greater contrast at a concentration of 127 mM, 254 mM, 381 mM, and 508 mM, respectively.Conclusion: These results suggest that the developed Triptorelin-Alginate-AuNPs may be considered an effectivecontrast agent for molecular CT imaging of gonadotropin-releasing hormone (GnRH) receptor-expressing cancer cells.